Primary screening of indigenous antagonist bacteria against Meloidogyne hapla larvae - S. N. Nekoval; M. N. Chernyakovich; V. S. Muraviev; A. K. Churikova (Юг России: экология, развитие)
Aim. To determine the nematicidal activity of native bacterial isolates from the rhizosphere of tomatoes affected by the northern root‐knot nematode Meloidogyne hapla.The study was carried out using bacterial isolates obtained from the rhizosphere of a tomato affected by meloidogynosis, the species of which was determined using DNA nucleotide sequence analysis. The analysis was carried out on a DNeasy Plant Mini Kit and the results were compared using the Unipro UGENE program. Nematicidal activity was calculated based on the number of dead nematodes counted using a microscope.From the rhizosphere of tomatoes infected with the northern root‐knot nematode Meloidogyne hapla, 10 isolates of antagonist bacteria were isolated into a pure culture and identified. To consider their safety for humans and warm‐blooded animals, 7 of these were tested for nematicidal activity. According to the data obtained, the use of 5 studied bacterial strains caused mass mortality of northern root‐knot nematode larvae, starting from 24 hours and reaching 92.2–97.2 % by 96 hours after the start of the experiment.Bacterial strains Bacillus thuringiensis IB17 (titer 1x105, CFU/ml), Pseudomonas silesiensis IB18 (titer 1x106, CFU/ml), Bacillus mycoides IB19 (titer 1x108, CFU/ml), Glutamicibacter arilaitensis IB23 (titer 1x106, CFU/ml), Pseudomonas silesiensis IB24 (titer 1x107, CFU/ml) exhibits high nematicidal activity against M. hapla larvae and can be used to create bionematicides.